Pengaruh Model Learning Cycle 5E Terhadap Kemampuan Menulis Resensi Pada Siswa Kelas XI SMA Negeri 8 Medan Tahun Ajaran 2023/2024 - Riza Risma Dewi (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to, (1) To determine the ability to write reviews in class XI students of SMA Negeri 8 Medan using the Conventional model, (2) To determine the ability to write reviews in class ) To determine the effect of the 5E Learning Cycle model on the ability to write reviews in class XI students at SMA Negeri 8 Medan. The population in this study were all class XI students, totaling 309 people. The sample consisted of 65 people who were divided into two classes, namely the control class with 32 people and the experimental class with 33 people. The instruments used in this research are the title, book identity, outline of the book's contents, book advantages, book weaknesses, closing review, spelling and punctuation, and neatness of writing. This research uses a two group test design experimental method using a quantitative approach. The data analysis techniques used are analysis requirements tests, normality tests, and hypothesis tests. The research results in writing reviews using the conventional model are in the fair category with an average value of 62. Meanwhile, the research results in writing reviews using the Learning Cycle 5E model are in the good category with an average value of 74. Through hypothesis testing, a t count of 18 is obtained. .05 > t table 1.66, this proves that there is a significant influence from the use of the Learning Cycle 5E model on the ability to write reviews in class XI students at SMA Negeri 8 Medan for the 2023/2024 academic year.